“ALFABETISM” IN MARKET TRANSFORMATIONS OF SOCIETY - Korzhenko V.V. (Pressing Problems of Public Administration, 2016)
The paper analyzes the problems of a modern transformation society in the process of establishing a market economy. The attention is focused on the essence and nature of the market environment knowledge (“alfabetism” in social cognition) and the speci c features of public administration.